Managed Evolution A Strategy for Very Large Information Systems - Murer, Stephan; Bonati, Bruno; Furrer, Frank J. (Springer Berlin Heidelberg Imprint: Springer, 2011)
Many organizations critically depend on very large information systems. In the authors' experience these organizations often struggle to find the right strategy to sustainably develop their systems. Based on their own experience at a major bank, over more than a decade, the authors have developed a successful strategy to deal with these challenges, including: - A thorough analysis of the challenges associated with very large information systems - An assessment of possible strategies for the development of these systems, resulting in managed evolution as the preferred strategy - Describing key system aspects for the success of managed evolution, such as architecture management, integration architecture and infrastructure - Developing the necessary organizational, cultural, governance and controlling mechanisms for successful execution.